Altered Expression of MBNL Family of Alternative Splicing Factors in Colorectal Cancer - Navvabi, Nazila; Kolikova, Pavla; Hosek, Petr; Zitricky, Frantisek; Navvabi, Azita; Vycital, Ondrej; Bruha, Jan; Palek, Richard; Rosendorf, Jachym; Liska, Vaclav; Pitule, Pavel (Cancer genomics & proteomics, 2021)
BACKGROUND/AIM: Colorectal cancer is currently the third leading cause of cancer-related deaths and recently, alternative splicing has risen as its important regulator and potential treatment target. In the present study, we analyzed gene expression of the MBNL family of regulators of alternative splicing in various stages of colorectal cancer development, together with the MBNL-target splicing events in FOXP1 and EPB41L3 genes and tumor-related CD44 variants. MATERIALS AND METHODS: Samples of tumor tissue and non-malignant mucosa from 108 patients were collected. After RNA isolation and reverse transcription, the relative gene expression of a selected gene panel was tested by quantitative real-time PCR, followed by statistical analysis. RESULTS: MBNL expression was decreased in tumor tissue compared to non-tumor mucosa. In addition, lower expression was observed for the variants of FOXP1 and EPB41L3, while higher expression in tumor tissue was detected both for total CD44 and its cancer-related variants 3 and 6. Transcript levels of the MBNL genes were not found to be related to any of the studied clinicopathological characteristics. Multiple significant associations were identified in the target gene panel, including higher transcript levels of FOXP1 and CD44v3 in patients with distant metastases and connections between recurrence-free survival and altered levels of FOXP1 and CD44v3. CONCLUSION: Our results identified for the first-time deregulation of MBNL genes in colorectal cancer. Down-regulation of their transcripts in tumor tissue compared to matched non-tumor mucosa can lead to transition of alternative splicing patterns towards a less differentiated phenotype, which highlights the importance of alternative splicing regulation for tumor growth and propagation.
Keywords: senioři; colorectal cancer; Cell Differentiation; kolorektální nádory; alternativní sestřih; Middle Aged; Colorectal Neoplasms; mužské pohlaví; RNA-binding proteins; Adult; Alternative splicing; RNA-Binding Proteins; ženské pohlaví; MBNL regulatory factors; Alternative Splicing; Humans; proteiny vázající RNA; lidé středního věku; buněčná diferenciace; dospělí; Female; Aged; lidé; Male